Occupancy based home automation system - Naga Siva Rao, K; K. Sreenivasa Ravi, Dr; Gopi Krishna, p (International Journal of Engineering and Technology, 2018)
Home automation is a component of â€œThe Internet of Things". Home automation has become modernized from many decades for the purport of controlling the abode appliances. In home automation we ourselves will predefine the commands for monitoring and controlling of home electrical appliances by which the energy is utilized effectively. Predicated on personal interest and cull utilizer can give his commands for controlling. Lot of energy is consumed by the electrical appliances even though there is no occupancy in a room. Occupancy is predicated proposed home automation system through which the cessation appliances are controlled and predicated based on the occupancy. In order to detect the occupancy PIR sensor is utilized which senses the heat radiations from an object and a kineticism is detected. Bluetooth predicated Android app is used to control the appliances on personal and to discard. The proposed system is a cost-effective system.Â